Difference between revisions of "009A Sample Final 2, Problem 1"
Jump to navigation
Jump to search
(Created page with "<span class="exam">Compute <span class="exam">(a) <math style="vertical-align: -15px">\lim_{x\rightarrow 4} \frac{\sqrt{x+5}-3}{x-4}</math> <span class="exam">(b) &nbs...") |
|||
Line 10: | Line 10: | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | |'''L'Hôpital's Rule''' | + | |'''L'Hôpital's Rule, Part 1''' |
|- | |- | ||
− | | | + | | |
+ | Let <math style="vertical-align: -12px">\lim_{x\rightarrow c}f(x)=0</math> and <math style="vertical-align: -12px">\lim_{x\rightarrow c}g(x)=0,</math> where <math style="vertical-align: -5px">f</math> and <math style="vertical-align: -5px">g</math> are differentiable functions | ||
|- | |- | ||
− | | | + | | on an open interval <math style="vertical-align: 0px">I</math> containing <math style="vertical-align: -5px">c,</math> and <math style="vertical-align: -5px">g'(x)\ne 0</math> on <math style="vertical-align: 0px">I</math> except possibly at <math style="vertical-align: 0px">c.</math> |
− | | ||
|- | |- | ||
− | | | + | | Then, <math style="vertical-align: -18px">\lim_{x\rightarrow c} \frac{f(x)}{g(x)}=\lim_{x\rightarrow c} \frac{f'(x)}{g'(x)}.</math> |
− | | ||
|} | |} | ||
Line 29: | Line 28: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We begin by noticing that we plug in <math style="vertical-align: 0px">x=4</math> into | + | |We begin by noticing that if we plug in <math style="vertical-align: 0px">x=4</math> into |
|- | |- | ||
| <math>\frac{\sqrt{x+5}-3}{x-4},</math> | | <math>\frac{\sqrt{x+5}-3}{x-4},</math> |
Latest revision as of 17:10, 20 May 2017
Compute
(a)
(b)
(c)
Foundations: |
---|
L'Hôpital's Rule, Part 1 |
Let and where and are differentiable functions |
on an open interval containing and on except possibly at |
Then, |
Solution:
(a)
Step 1: |
---|
We begin by noticing that if we plug in into |
we get |
Step 2: |
---|
Now, we multiply the numerator and denominator by the conjugate of the numerator. |
Hence, we have |
(b)
Step 1: |
---|
We proceed using L'Hôpital's Rule. So, we have |
|
Step 2: |
---|
Now, we plug in to get |
(c)
Step 1: |
---|
First, we have |
Step 2: |
---|
Now, |
Final Answer: |
---|
(a) |
(b) |
(c) |